2011
DOI: 10.1021/pr200333f
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Protective Role of Nitric Oxide against Salt Stress at the Physiological and Proteomic Levels in Maize

Abstract: Saline stress is a major factor that limits crop yield. Nitric oxide (NO) is functional during plant growth, development, and defense responses. In the present study, the protective role of NO in alleviating saline stress in maize at the physiological and proteomic levels was examined. Our results showed that salt treatment quickly induced NO accumulation and addition of the NO donor S-nitroso-N-acetylpenicillamine (SNAP) efficiently eliminated the inhibitory effect of salt on shoot growth and photosynthesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 41 publications
4
80
0
Order By: Relevance
“…Discussion DETA/NO was successfully used to elevate the endogenous NO level and reduce salt-induced damage in maize (Keyster et al, 2012). This effect could be reversed by NO metabolic scavengers and inhibitors (Bai et al, 2011). In the present study, the protective role of NO against salt stress was confirmed in maize using DETA/NO and by inhibiting its synthesis with l-NNA.…”
Section: Gene Expression Studiessupporting
confidence: 64%
See 1 more Smart Citation
“…Discussion DETA/NO was successfully used to elevate the endogenous NO level and reduce salt-induced damage in maize (Keyster et al, 2012). This effect could be reversed by NO metabolic scavengers and inhibitors (Bai et al, 2011). In the present study, the protective role of NO against salt stress was confirmed in maize using DETA/NO and by inhibiting its synthesis with l-NNA.…”
Section: Gene Expression Studiessupporting
confidence: 64%
“…NO enhanced salt tolerance in maize due to the activation of proton pumps and the Na + /H + antiport, as indicated by improved growth, increased dry matter accumulation and greater chlorophyll content (Zhang et al, 2006). The protective https://repository.uwc.ac.za/ effect of NO against salt stress in maize can also be linked to the enhanced activity of antioxidant enzymes (Bai et al, 2011;Keyster et al, 2012). The induction of various antioxidant enzymes (catalase, APX, SOD) by NO was also observed under salt stress in chickpea (Sheokand et al, 2008), wheat (Zheng et al, 2009) and rice (Uchida et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…NO production is altered when plants are subjected to abiotic or biotic stresses (13,14). High salt, a major environmental factor that limits agriculture yield, induces a quick endogenous NO accumulation in plants (15,16), and triggers enhanced Na + influx and reduced K + absorption in the root (17). Both endogenously produced NO and exogenously applied NO have been proposed to enhance plant salt tolerance (18-21) by attenuating high saltinduced increases in the Na + to K + ratio.…”
mentioning
confidence: 99%
“…Arfan (2009) reported that, SAinduced SOD activity accompanied with an increase in shoot Ca 2 + supported the view that if sufficient Ca 2 + is present, it acts as a second messenger and causes a transient increase in H 2 O 2 , which in turn induces antioxidant enzymes leading to decrease in ROS on long-term basis. It has also been reported that NO treatment further improved protein accumulations and enzyme activities including APX, Mn-SOD, GR, and growth via G proteins (Bai et al 2011).…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, an efficient H 2 O 2 scavenging system is Simaei et al 2011). Bai et al (2011) found that NO affected a series of protein accumulation involving in material and energy metabolism, including ATPase and LOX.…”
Section: Discussionmentioning
confidence: 99%